1986
DOI: 10.1111/j.1365-3083.1986.tb02088.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Defect of Phagocytic Cell Function in Subjects at Risk for Acquired Immunodeficiency Syndrome

Abstract: We studied the functions of peripheral blood monocytes and polymorphonuclear cells in 15 apparently healthy homosexual men, eight homosexual or bisexual subjects with unexplained generalized lymphadenopathies (pre-AIDS), four homosexual men with acquired immunodeficiency syndrome (AIDS), and 15 heterosexual men. In comparison with normal controls, the homosexual groups studied presented a decreased monocyte candidacidal activity for Candida pseudotropicalis that gradually deteriorates as the clinical symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Impaired phagocytosis and bacteriocidal process of the phagocytes of AIDS patients have been reported from a number of laboratories [Fauci, 1984;Bender et al, 1985;Estevez et al, 1986;Roux-Lombard et al, 1986;Moller et al, 1990;Pos et al, 1992]. Macrophages are the major phagocytic and antigen presenting cells.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired phagocytosis and bacteriocidal process of the phagocytes of AIDS patients have been reported from a number of laboratories [Fauci, 1984;Bender et al, 1985;Estevez et al, 1986;Roux-Lombard et al, 1986;Moller et al, 1990;Pos et al, 1992]. Macrophages are the major phagocytic and antigen presenting cells.…”
Section: Introductionmentioning
confidence: 99%
“…They found NBT reduction as stimulated by PMA and zymosan to be impaired in both groups compared with controls. A more recent study also found the chemoluminescence response to zymosan of peripheral blood monocytes from HIV-infected patients to be lower than that of controls in a 60-min assay (9). Alveolar macrophages from pediatric ARC patients were reported to release more HP at both baseline levels and after stimulation with PMA (5 ng/L) than a control group, although the assay was run for only 30 min.…”
Section: Discussionmentioning
confidence: 94%
“…The monocyte candidacidal activity for Candida pseudotropicalis in HIV-infected patients was reported to be impaired and deteriorated further in patients with more advanced disease (9). Monocyte-derived macrophages infected with HIV in vitro were also reported to be defective in killing C. pseudotropicalis (22).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators (Murray et al, 1985;Washburn, Tuazon & Bennett, 1985;Nielsen, Kharazmi & Faber, 1986) found that intracellular killing by monocytes was normal. Others (Estevez et al 1986;Bales, Moshtael & Pinching, 1987) have shown loss of microbicidal activity in mononuclear phagocytes from patients with HIV infection, Microbicidal activity of monocytes and macrophages is heavily dependent on the generation of reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the monocyte-macrophage system in the pathogenesis of HIV infection has been established during the last years, Monocytes and macrophages can be infected by HIV in vitro, and HIV can be recovered from monocytes and macrophages obtained from blood and various organs of HIVinfected individuals (Levy et al, 1985;Gartner et al, 1986;Ho, Rota & Hirsch, 1986;Nicholson et al, 1986;Salahuddin et al, 1986), Various functional abnormalities of monocytes and macrophages have been reported in patients with HIV infection, including abnormal secretion of monokines (Wright et al, 1988;Fauci, 1988;Breen et al, 1990), defective chemotaxis (Smith et al, 1984;Poli et al, 1985) and reduced Fc and C3 receptormediated phagocytosis (Bender et al, 1988),…”
Section: Introductionmentioning
confidence: 99%